Study on the Relationship between Symbolic Immortality and Population - Xianghan MENG; Qiang LI (Yixue yu zhexue)
This study employs multidisciplinary lenses from psychology, sociology, and cultural studies to examine the explanatory mechanisms of symbolic immortality theory in understanding demographic behaviors and its contemporary challenges. Theoretical frameworks including symbolic immortality theory, terror management theory, the sense of generativity, and legacy theories collectively reveal humanity's profound need to transcend biological finitude through strategies such as procreation, cultural production, and collective memory. However, the traditional "procreation-immortality" logic faces deconstruction in modern contexts: intergenerational ethics is undermined by cultural integration dilemmas; materialistic values exacerbate the imbalance between rising parental costs and diminishing psychological returns; technological revolutions enable potential physical/consciousness immortality, sparking ethical controversies surrounding digital immortality. Subsequent research should elucidate the conceptual framework and function of symbolic immortality, promote localized strategies and theoretical development, and concentrate on the symbolic immortality issues in marginalized or special populations.